Digital microfluidics-like manipulation of electrokinetically preconcentrated bioparticle plugs in continuous-flow. Issue 4 (26th January 2022) - Park, Sinwook; Sabbagh, Barak; Abu-Rjal, Ramadan; Yossifon, Gilad
Abstract : Schematic presentation of digital microfluidics-like manipulation of a single (top panel) and multiple (bottom panel) preconcentrated bioparticle plugs. Abstract : Herein, we demonstrate digital microfluidics-like manipulations of preconcentrated biomolecule plugs within a continuous flow that is different from the commonly known digital microfluidics involving discrete ( i.e. droplets) media. This is realized using one- and two-dimensional arrays of individually addressable ion-permselective membranes with interconnecting microfluidic channels. The location of powered electrodes, dictates which of the membranes are active and generates either enrichment/depletion diffusion layers, which, in turn, control the location of the preconcentrated plug. An array of such powered membranes enables formation of multiple preconcentrated plugs of the same biosample as well as of preconcentrated plugs of multiple biosample types introduced via different inlets in a selective manner. Moreover, digital-microfluidics operations such as up-down and left–right translation, merging, and splitting, can be realized, but on preconcentrated biomolecule plugs instead of on discrete droplets. This technology, based on nanoscale electrokinetics of ion transport through permselective medium, opens future opportunities for smart and programmable digital-like manipulations of preconcentrated biological particle plugs for various on-chip biological applications.